Effect of Ion Irradiation on the Mechanical Properties of High and Low Copper - H.M. Qadr (PPIKSN-BATAN, 2020)
An investigation into the effects of proton beam exposure on high- and low-copper structural materials for nuclear reactors has been carried out. The aim of this work was to investigate the impact of proton energy irradiation on the damage of the materials. The damage parameter used in the evaluation was displacement per atom (dpa) in material as a function of proton energy. In addition, a TRIM code was used to identify the penetration depth in response to changes in proton energy. The effect of proton beam exposure on the irradiation induced hardening of the different copper levels was investigated by Vickers Hardness tests for microstructural changes examination. The proton beam incident energy was 3 MeV and the temperature was kept at approximately 30 ᴼC. A 25 μm flat damage profile was achieved at 0.367 and 0.373 dpa for low and high copper samples, respectively. The hardness variation with depth and yield strength variation with dose (dpa) were also investigated. Based on the results, the study found that the hardness test for the high copper was higher than the low copper.